The Lioness of African Music: Cultural Interpretation of Wiyaala’s Stage Costume Art - navei, Nyamawero (International Journal of Culture and Art Studies, 2023)
In stage performance, costume art is an essential visual signature device with the veracity to unveil the character and cultural identity of the performer. Stage costume art could also be deployed to respond to pertinent societal issues. In spite of its versatile essentiality in performing arts, there seems to be a dearth of scholarly interpretation of stage costume art of Ghanaian musicians, thereby creating a knowledge gap. This qualitative case study makes a hermeneutical interpretation of eight random-purposively sampled stage costumes of Wiyaala (a Ghanaian female musician) to establish their cultural symbolism. The study found Wiyaala not only an iconic Ghanaian artiste but an internationally recognised musician who toured many countries across Africa, Europe, the Americas, and other continents for musical stage performances. It emerged that Wiyaala’s stage costumes were locally self-constructed, and ably reflected the uniquely versatile indigenous African (Ghanaian) dress cultural identity in respect of African (Ghanaian): royal dress fashion, war costumes, initiation costumes, and others. Wiyaala could be said to have prioritised interest in using her locally sourced stage costume art to promote and preserve indigenous African (Ghanaian) dress cultural identity. Since Wiyaala is an iconic musician, she is encouraged to continue deploying locally sourced costume art for her stage performances to promote and preserve African (Ghanaian) dress cultural identity for posterity. This tends to decolonise the stage costume choice of many Ghanaian musicians with its cascading impact on the Ghanaian textile and fashion industry for economic and job gains.